(3TQM cJGH MQa GddGe ddTjN GdQFjS Hf SjfG Ydi Hf GdMSjf GHf YHOGddgs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3bGd ZQVg Hbhdg Ef cGfJ GdLhGgQ aGSOI aGdcd aGSO Cf KHJ GdeaGQb ddeGOI s
(3BNQgG (B:s
(3de jcf GdhLhO eTJed Ydi LejY GfMGA GdhLhO GdeecfI bHd GdhUhd Edi NjQ Gdchf hGdaSGO s
(3Vef eLehY , JQJjHgG (B: (3GdQGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3MceI JjehQ (B86) s
Keywords: (3GdadSaI hGdefWbs